Comunicação pública da ciência no ensino superior: diagnóstico preliminar e proposições sobre a divulgação científica na Universidade Federal de Uberlândia - Anjos, Mayara Abadia Delfino dos (2015)
This research examined the public communication of science in higher education, specifically in the Federal University of Uberlândia. The work of the corpus consist with literature review on public communication policies, communication plan, information and communication flows, public communication in HEIs, scientific communication in HEIs, observation group of the university, research sites and documents institution, interview with the rector of the institution and director of the communication department. From all this data collected, it was possible to verify that the Federal University of Uberlândia practice public communication of science, as proposed by the literature and its experts. The results showed that there are many problems in information flows at the University and this should be improved to, in fact, communication is practiced as they say theories, in order to achieve results through communication. There have been some proposals to improve these flows and presented a process flow diagram for a better quality of public communication in development processes of science.